Study of the B+→J/ψΛ¯pB+→J/ψΛ¯p decay in proton-proton collisions at √s = 8 TeV; Journal of High Energy Physics; Vol. 2019, iss. 12 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen